Examining the impact of lean manufacturing on soft TQM practices and sustainable performance: evidence from Malaysian Industries - Khalili, Amjad; Ismail, Md Yusof; Rahman, Mohammad Mustafizur; Che Daud, Mohd Radzi (IEOM Society, 2017)
Sustainable Performance (SP) is a common goal for any manufacturing organization. In this regard a conceptual model is developed in this paper to investigate the impact of Lean Manufacturing (LM) on Soft TQM (STQM) practices and Malaysian industries SP. Little empirical studies are conducted in the developing economy of Malaysia to examine the interrelationships among these three (3) key Operations Management (OM) practices. The primary data which gathered from 329 Malaysian industries through a structured questionnaire were analyzed using techniques from Structural Equation Modeling (SEM). Findings from AMOS 22 program implied that two (2) hypotheses are supported which indicated that these are complementary practices. These are associated with LM and STQM and LM and SP. On the other hand, hypothesis related to STQM and SP relationship is not supported which implied that future researchers have to focus more on TQM tools and techniques.